2015
DOI: 10.3928/1081597x-20150521-11
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Corneal Collagen Cross-Linking in Thin Keratoconic Corneas

Abstract: The results of this study revealed that accelerated corneal collagen cross-linking stabilized the progression of keratoconus without a significant endothelial cell density loss during the 12 months of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 27 publications
2
27
0
2
Order By: Relevance
“…They found small but insignificant improvements in UDVA (0.11 logMAR) and CDVA (0.30 logMAR). 19 Similar to our results, Vinciguerra et al 20 observed UDVA (0.17 logMAR) and CDVA (0.22 logMAR) improvements in month 6 of conventional corneal CXL. In addition, they determined that visual acuity did not change after 6 months.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…They found small but insignificant improvements in UDVA (0.11 logMAR) and CDVA (0.30 logMAR). 19 Similar to our results, Vinciguerra et al 20 observed UDVA (0.17 logMAR) and CDVA (0.22 logMAR) improvements in month 6 of conventional corneal CXL. In addition, they determined that visual acuity did not change after 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…The analysis included 49 eyes from 43 patients (25 males, 18 females) with a mean age of 21.2 6 7.1 (range: [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Before the surgery, the mean corneal thickness was 404 6 18 mm, and the thickness was reduced to 360 6 24 mm after removing the epithelium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these it has been now suggested that usage of HPMC (Hydroxypropyl methylcellulose) riboflavin 26 helps prevent corneal dessication induced by dextran and could be considered in borderline cases. Other methods by which dessication could be reduced are using accelerated CXL 27 and eyelid closure 28 during the initial riboflavin instillation. All of these combined can work in borderline pachymetry without any specialized technique.…”
Section: Modification Of Parameters During CXLmentioning
confidence: 99%
“…As stromal thickness is often less than 400 μ m in advanced keratoconus (stage III Amsler – Krumeich classification), modifications of the standard protocol have been suggested (Padmanabhan & Dave ; Raiskup & Spoerl ) including higher riboflavin concentration in the photosensitizer solution, increase of the riboflavin film thickness, downregulation of the UVA surface irradiance, shorter irradiation time with a higher UVA irradiance (AXL with ‘steak effect’; Ozgurhan et al. ), swelling the stroma by hypoosmolar solutions (Hafezi et al. ) and customized epithelial debridement cross‐linking (‘epithelial island technique’; Kymionis et al.…”
Section: Introductionmentioning
confidence: 99%